2020
DOI: 10.1109/mcom.001.2000310
|View full text |Cite
|
Sign up to set email alerts
|

THz Radio Communication: Link Budget Analysis toward 6G

Abstract: How well do upper millimeter-wave and terahertz frequency bands enable wireless communications? In this work, we approximate the current and estimate the future communication potential with emphasis on antenna and radio frequency hardware technologies, and radio propagation challenges. This is done by performing link budget evaluations with justified estimates of link budget calculus terms, such as the achievable or required noise figure, transmit power, and antenna gain. Estimates are based on current enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(64 citation statements)
references
References 8 publications
0
64
0
Order By: Relevance
“…[34] Oct. Survey A comprehensive study of 6G visions, requirements, challenges, and open research issues, outlining seven disruptive technologies, i.e., millimeter wave (mmWave) communications, THz communications, optical wireless communications, programmable meta-surfaces, drone-based communications, back-scatter communications, and Tactile Internet. [35] Nov. THz Analyzes link budget of THz links with justified estimates of calculus terms, such as the achievable or required noise figure, transmit power, and antenna gain. [36] Nov. THz Discusses full protocol stack for the realization of end-to-end terahertz 6G mobile networks, from medium access control, network to transport layer.…”
Section: Feb Vehicularmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Oct. Survey A comprehensive study of 6G visions, requirements, challenges, and open research issues, outlining seven disruptive technologies, i.e., millimeter wave (mmWave) communications, THz communications, optical wireless communications, programmable meta-surfaces, drone-based communications, back-scatter communications, and Tactile Internet. [35] Nov. THz Analyzes link budget of THz links with justified estimates of calculus terms, such as the achievable or required noise figure, transmit power, and antenna gain. [36] Nov. THz Discusses full protocol stack for the realization of end-to-end terahertz 6G mobile networks, from medium access control, network to transport layer.…”
Section: Feb Vehicularmentioning
confidence: 99%
“…Recently, Bariah et al gave a comprehensive 6G vision in [34], identifying seven disruptive technologies, associated requirements, challenges, and open research issues. From the viewpoints of radio frequency (RF) hardware and antenna, [35] analyzes link budget of THz communication links with justified estimates of calculus terms, such as the achievable or required noise figure, transmit power, and antenna gain. It also evaluates communication distances for links implemented with different technologies and complexity at 300 GHz looking towards anticipated 6G use scenarios.…”
Section: Feb Vehicularmentioning
confidence: 99%
“…It has been widely acknowledged that the trend in the evolution of wireless communication systems is toward higher data rates, system capacities, carrier frequencies, and bandwidths [1]. After the employment of millimeter-wave (mmWave) by the fifth-generation wireless communication system (5G), future sixthgeneration wireless communication system (6G) [2] are foreseen to utilize upper mmWave band (100-300 GHz) and terahertz (THz) band (0.1-10 THz) frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…According to the prediction of the ITU, the demand of data rate in the wireless networks will even reach terabit (Tbit) per second by 2030 [5]. To target this, many studies have suggested that the terahertz (THz) technique is one of potential key enabling technologies in 6G [6][7][8]. Indeed, the THz frequency band (0.1-10 THz) has the potential to carry information at a scale of terabit (Tbit, 1Tbit/s=1000Gbit/s) [9,10].…”
Section: Introductionmentioning
confidence: 99%